(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2018)
The article on the basis of accounting of natural fodder agricultural lands, statistical data about consumption of basic food products by population, import of cattle-farming production, dynamics of cattle livestock, the analysis of their use as to economic, ecological, and social aspects is conducted. Analysing the given data we can make a conclusion that density of cattle livestock on agricultural lands decreased more than six times leading to catastrophic decrease of using organic fertilizers and worsening the quality of plant growing products. Decrease of cattle livestock led to rising in price products and increase of its consumption. At the same time (2010–2015) in average Ukraine imported on 673 864 thousand dollars meat and meat products and milk and milk products that is equivalent more than 18 mlrd grn. The cost of livestock products in Ukraine was 71,03 mlrd grn in 2015. The efficiency of using land resources has a big meaning in economy of country agriculture. The increase of quantity and quality of cattle farming products may be successfully realized only on conditions of important increase of efficiency of using land resources that acquires special topicality in modern state of conducting agriculture. The carrying out of given measures will lead to import substitution of cattle farming products that will give possibility to create in agricultural farms additionally more than 34 thousand of working places and will increase the receipts of means to personal farms of rural dwellers on 9,8 mlrd grn. The given measures will give the possibility to improve the social and economic situation in rural locality